2019
DOI: 10.1093/ce/zkz025
|View full text |Cite
|
Sign up to set email alerts
|

A case study of digital-twin-modelling analysis on power-plant-performance optimizations

Abstract: China Energy’s National Institute of Clean-and-Low-Carbon Energy (NICE) is developing a Power Plant Smart Management (PPSM) platform that employs digital-twin technology to undertake techno-economic modelling analysis on China Energy’s existing coal-fired power-plant units and explore cost-effective solutions to improve those plant units’ thermal efficiencies and operating performance. This paper presents a case study of PPSM on a 320-MWe coal-fired thermal power-plant unit, demonstrating how the digital-twin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Digital twins of energy assets 13 [9][10][11][12][13][14][15][16][17][18][19][20][21] Energy forecasting 14 [1,[22][23][24][25][26][27][28][29][30][31][32][33][34] Optimization and coordination 18 [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] VPP applications in smart grids Energy services delivery 31 [4,5,22,35,38, Local energy autonomy 21 [5,…”
Section: Vpp Concepts and Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Digital twins of energy assets 13 [9][10][11][12][13][14][15][16][17][18][19][20][21] Energy forecasting 14 [1,[22][23][24][25][26][27][28][29][30][31][32][33][34] Optimization and coordination 18 [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] VPP applications in smart grids Energy services delivery 31 [4,5,22,35,38, Local energy autonomy 21 [5,…”
Section: Vpp Concepts and Technologymentioning
confidence: 99%
“…A user's DT profile seamlessly incorporates their flexibility profiles, representing the selected flexibility assets, and can increase the "smartness level" of buildings which will lead to increased participation in energy flexibility services to be delivered by the VPP [17]. The modeling techniques' focus is not just on the average dynamics but also on modeling uncertainty, i.e., a statistical description of stochastic behavior, as it has a severe impact on any decision-making logic on VPP optimization [18]. In holistic terms, the DT can consider the consumer's profile in terms of behavior and incentive mechanisms of VPPs along with their community aggregation association and flexibility assets reflecting various commodities (electricity, biogas, heat) [19].…”
Section: Digital Twins' Modelsmentioning
confidence: 99%
“…General Electric Co. GE used DT to optimize the whole process of wind farm development, operation, and maintenance to improve the plant's profitability and sustainability [171] . Siemens created an asset and operation management system as a DT model for Fingrid, Electrical Verkko Information System, which connects a network model and measurement database automatically via an interface [172] . Additionally, Xu et al suggested that DT technology can help search and analyze costeffective approaches to power plant smart management and presented a specific example of a 320-MWe coal-fired generating system [173] .…”
Section: Energy Applicationsmentioning
confidence: 99%
“…Although DT and CPS can offer numerous advantageous features to the economic performance of a system, the cost associated with the implementation of these data-driven technologies is often overlooked. For example, numerous past studies that have conducted TEA on DT (Xu et al, 2019;Gerogiorgis and Castro-Rodriguez, 2021;Koulouris et al, 2021) and CPS (Zhao et al, 2019) incorporated only processes, taking into account the cost associated with production processes (i.e., equipment cost, contractor's fee, etc. ), while ignoring the cost required to set-up these smart technologies.…”
Section: Cloud Computingmentioning
confidence: 99%